Documenting China's Garment Industry: Wang Bing's Portrayal of Migrant Workers' Suspended Lives within the Contract Labour System - van der Meulen, Sjoukje (University of British Columbia, 2021)
This essay examines two films by the Chinese documentary filmmaker Wang Bing about temporary migrant workers in small, privately owned garment workshops in Zhejiang Province, China: Bitter Money (Ku Qian; 2016) and 15 Hours (Shi Wu Xiao Shi; 2017). Wang’s films portray Chinese garment workers’ lived experiences of “suspension,” as defined by Biao Xiang in this issue, in unique cinematic ways. Social sciences have paid close attention to the experiences of migrant workers, but art documentaries use audiovisual and aesthetic means to explore their everyday reality, producing what D. MacDougall calls distinctive “affective knowledge.” Wang’s films are usually categorized as part of the Sixth Generation of Chinese filmmakers, known for capturing social issues through observational methods. In this essay, I identify Wang’s works with the aesthetics of “slow cinema” and a global documentary trend in the visual arts as theorized by T. J. Demos in The Migrant Image. Based on close observation coupled with empathetic insight, Wang develops his own subjective method to portray people in a transformed and still changing China, where suspension is a common state of being. Ultimately, Wang’s films not only make the personal experiences of migrant workers visible and tangible, but also problematize their underlying, collective condition of suspension due to the contract labour system and associated hypermobility. The suspension approach suggests a productive way of bringing documentary art and social sciences into dialogue.
Keywords: Floating population; Garment industry; Hypermobility; Migrant image; Migration; Slow cinema; Suspension; Wang Bing; Taverne; Geography, Planning and Development; Sociology and Political Science